Expression of human carcinoembryonic antigen‐related cell adhesion molecule 6 and alveolar progenitor cells in normal and injured lungs of transgenic mice. Issue 12 (23rd December 2015) - Lin, Shin‐e; Barrette, Anne Marie; Chapin, Cheryl; Gonzales, Linda W.; Gonzalez, Robert F.; Dobbs, Leland G.; Ballard, Philip L.
Abstract: Carcinoembryonic antigen‐related cell adhesion molecule 6 (CEACAM6) is expressed in the epithelium of various primate tissues, including lung airway and alveoli. In human lung, CEACAM6 is developmentally and hormonally regulated, protects surfactant function, has anti‐apoptotic activity and is dysregulated in cancers. We hypothesized that alveolar CEACAM6 expression increases in lung injury and promotes cell proliferation during repair. Studies were performed in CEABAC transgenic mice‐containing human CEACAM genes. The level of CEACAM6 in adult CEABAC lung was comparable to that in human infants; expression occurred in epithelium of airways and of some alveoli but rarely co‐localized with markers of type I or type II cells. Ten days after bleomycin instillation, both the number of CEACAM6 + cells and immunostaining intensity were elevated in injured lung areas, and there was increased co‐localization with type I and II cell markers. To specifically address type II cells, we crossed CEABAC mice with animals expressing EGFP driven by the SP‐C promoter. After bleomycin injury, partially flattened, elongated epithelial cells were observed that expressed type I cell markers and were primarily either EGFP + or CEACAM6 + . In cell cycle studies, mitosis was greater in CEACAM6 + non‐type II cells versus CEACAM6 + /EGFP + cells. CEACAM6 epithelial expression was also increased after hyperoxic exposure and LPS instillation, suggesting a generalized response to acute lung injuries. We conclude that CEACAM6 expression is comparable in human lung and the CEABAC mouse. CEACAM6 in this model appears to be a marker of a progenitor cell population that contributes to alveolar epithelial cell replenishment after lung injury. Abstract : Transgenic mice containing human Carcinoembryonic Cell Adhesion Molecule genes express CEACAM6 in selected, unidentified lung epithelial cells at levels comparable to the human infant. Expression is increased in three models of lung injury with some localization to epithelial cells expressing both type 1 and type 2 cell markers. We propose that CEACAM6 in this model is a marker of a progenitor cell population that contributes to alveolar epithelial cell replenishment after lung injury.